Transmission (The Invasion Chronicles-Book One): A Science Fiction Thriller - Morgan, Rice (Lukeman Literary, 2018)
"TRANSMISSION is riveting, unexpected, and firmly rooted in strong psychological profiles backed with thriller and sci-fi elements: what more could readers wish for? (Just the quick publication of Book Two, Arrival.)" --Midwest Book Review From #1 worldwide bestselling fantasy author Morgan Rice comes a long-anticipated science fiction series debut. When SETI finally receives a signal from an alien civilization, what will happen next? A 13 year old boy, dying of a rare brain disease, is the only one able to hear and decode signals from outer space. SETI confirms it is a real signal. What is the message? How will the world react? And most of all: are the aliens coming? "Action-packed .... Rice's writing is solid and the premise intriguing." -Publishers Weekly, re A Quest of Heroes "A superior fantasy... A recommended winner for any who enjoy epic fantasy writing fueled by powerful, believable young adult protagonists." -Midwest Book Review, re Rise of the Dragons "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as THE INHERITANCE CYCLE by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." -The Wanderer, A Literary Journal (regarding Rise of the Dragons) Book #2 in the series-ARRIVAL-is also available for pre-order! Also available are Morgan Rice's many series in the fantasy genre, including A QUEST OF HEROES (BOOK #1 IN THE SORCERER'S RING), a free download with over 1,300 five star reviews!
Keywords: Young Adult, New Adult